1995
DOI: 10.2105/ajph.85.10.1412
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Medicaid child health screenings: the effectiveness of mailed pamphlets, phone calls, and home visits.

Abstract: OBJECTIVES. A randomized controlled trial was conducted to test the effectiveness and cost effectiveness of three outreach interventions to promote well-child screening for children on Medicaid. METHODS. In rural North Carolina, a random sample of 2053 families with children due or overdue for screening was stratified according to the presence of a home phone. Families were randomly assigned to receive a mailed pamphlet and letter, a phone call, or a home visit outreach intervention, or the usual (control) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…A 0% non-participation rate was only achieved in 11 out of 64 studies (17%). [104][105][106][107][108][109][110][111][112][113][114] Seven of the 65 included studies (11%) had non-participation rates of 50% or more, which could have consequences for the external validity of their results. [115][116][117][118][119][120][121] Where nonparticipation rates were high it is possible that those who participated in the study were more agreeable to attending screening or differed in a number of other ways from those who did not participate.…”
Section: Non-participation Ratementioning
confidence: 99%
See 1 more Smart Citation
“…A 0% non-participation rate was only achieved in 11 out of 64 studies (17%). [104][105][106][107][108][109][110][111][112][113][114] Seven of the 65 included studies (11%) had non-participation rates of 50% or more, which could have consequences for the external validity of their results. [115][116][117][118][119][120][121] Where nonparticipation rates were high it is possible that those who participated in the study were more agreeable to attending screening or differed in a number of other ways from those who did not participate.…”
Section: Non-participation Ratementioning
confidence: 99%
“…Twenty-three studies had follow-up rates of 100%. 68,[71][72][73]76,85,87,91,94,96,101,102,104,106,107,109,110,112,114,119,121,123,124 Those studies that had a high follow-up rate tended to use smaller sample sizes; thus they lacked power and may not be very representative of the target population. Nine of the studies that had follow-up rates of 95% or more, however, included less than 300 participants.…”
Section: Assessment Of Determinantsmentioning
confidence: 99%
“…The Use of EPSDT Services by Medicaid Children purpose was to motivate parents to seek EPSDT visits for their children (Oda, Heilbron, and Taylor 1995;Selby-Harrington et al 1995).…”
Section: Previous Researchmentioning
confidence: 99%
“…Selby-Harrington et al 13 found the use of a mailed pamphlet or letter, a phone call, or a home visit to be minimally effective in increasing well child screening visits. Laken and Ager 14 found that giving patients money as an incentive did not improve their prenatal clinic missed appointment rate.…”
Section: Discussionmentioning
confidence: 99%